Discovery Routing Time Speed Comparison of AODV, OLSR and ZRP protocols on MANET - Safrianti, Ery; Oktaviana Sari, Linna; Rahayu, Tulus (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2020)
Mobile Ad hoc Network (MANET) is a wireless network that contains a collection of nodes without infrastructure and interconnected to communicate. MANET works dynamically when a group of nodes moves spontaneously, so the network topology can change quickly and cannot be predicted. It causes changes in wireless network topology according to existing conditions. The node functions in determining the route to be selected. Ad Hoc networks have limited transmission range, so routing is needed to send data over the network. The problem with mobile nodes is that routing must provide a path when the node changes. The speed of a node obtaining information is affected by the routing protocol used in the network. Each routing protocol has different capabilities in network speed, so the discovery routing time for each routing is also different. The selected routing protocols are Ad Hoc On-Demand Distance Vector (AODV), Optimized Link-state (OLSR), and Zone Routing Protocol (ZRP). The study will conduct a comparative analysis of ad hoc network initialization speeds on AODV, OLSR, and ZRP routing protocols. The parameter tested is the speed of routing discovery. After the data is collected, an analysis is carried out by looking at the routing discovery speed of each routing protocol. The test results show that each of the routing protocols examined, the AODV routing protocol, has a faster routing discovery time than the OLSR and ZRP routing protocols.